PENGELOLAAN KELAS ANAK BERKEBUTUHAN KHUSUS DI TK ISLAM PEMBANGUNAN - Hasanah; Nurmalasari (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
The purpose of this research is to determine classroom management in inclusive schools at the Islamic Development Kindergarten, such as learning planning, the learning implementation process and learning evaluation. The method used in this research is Qualitative Descriptive, namely direct observation and description. In this research, the data collection techniques used to collect the data needed by researchers are by means of observation, interviews and documentation. The results of this research on managing the learning process for ABK in inclusion classes at the Islamic Development Kindergarten, it can be concluded that learning management for ABK students in inclusion classes is carried out in the form of managing learning planning, learning implementation and assessing learning outcomes. The learning management carried out includes using the regular curriculum by differentiating achievement indicators for ABK students, the implementation of learning is accompanied by GPK, there is seating management, and the assessment of learning outcomes is the same for ABK and non-ABK students in terms of method, but different in the final form of assessment